The Arctic and Antarctica: Greenland Research Trips 2012 and 2015. - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions. Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the contemporary Sublime. This item documents Neudecker's 2 research trips to Greenland, the first in 2012 that included a 5 day expedition with Inuit subsistence hunters, and the second in 2015 with Project Pressure to document receding glaciers. The research conducted on both trips had a significant impact on the development of subsequent works and exhibitions.Also included in this item is Lamentations, a brief essay by Neudecker reflecting on her experience during her first Greenland expedition and is included in Hinterland , a collection of essays about her work which was published by the Trondheim Kunstmuseum, in 2014. and was edited by Pontus Kyander, Director of Trondheim Kunstmuseum, Norway. Photography by Mariele Neudecker. Images used with permission. A feature in the Guardian's In Pictures documents Neudecker's visit in Greenland Glaciers through an artist's eyes: https://www.theguardian.com/environment/gallery/2016/feb/25/greenland-glaciers-mariele-neudecker-klaus-thymann-project-pressure The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.